Menghadapi Tantangan Administrasi di tempat Magang ( CV Griya Persada Engineering ) - Meisy Nanik Isdaryati; Zsa Zsa Izazi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Internships are a valuable opportunity for students to apply the theoretical knowledge they have acquired in college into real practice in the world of work. However, this process does not always run smoothly, especially when faced with various administrative challenges. This article discusses the main challenges often encountered by internship students in the administrative field, such as difficulties in time management, adapting to new office systems and procedures, and inter-departmental communication and coordination. Through case study methods and interviews with intern students, this article identifies effective solutions and strategies to overcome these obstacles. It was found that guidance from mentors, intensive training before internships, and the application of digital technology in administrative tasks can significantly improve the internship experience and students' readiness to enter the world of work. It is hoped that the results of this research can provide insight for educational institutions and companies in designing internship programs that are more effective and beneficial for students.